2022
DOI: 10.1038/s41563-022-01431-x
|View full text |Cite|
|
Sign up to set email alerts
|

Tissue fluidification promotes a cGAS–STING cytosolic DNA response in invasive breast cancer

Abstract: The process in which locally confined epithelial malignancies progressively evolve into invasive cancers is often promoted by unjamming, a phase transition from a solid-like to a liquid-like state, which occurs in various tissues. Whether this tissue-level mechanical transition impacts phenotypes during carcinoma progression remains unclear. Here we report that the large fluctuations in cell density that accompany unjamming result in repeated mechanical deformations of cells and nuclei. This triggers a cellula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 69 publications
0
37
0
Order By: Relevance
“…According to our previous study, [ 17 ] we propose that cancer cell clusters with an increasing amount of unjammed cells lead to decreased stiffness and increased fluidity . A recent study [ 97 ] has shown that on the cellular level, the repeated mechanical deformations associated with tissue fluidization by unjamming trigger mechano‐protective mechanisms that lead to the formation of perinuclear actin rings and result in increased nucleus size and stiffness and furthermore, that due to the increased stress and strains unjammed cells are more prone to nuclear envelope rupture and consequential DNA damage, which further increases their malignancy. The unjammed cells showed also an upregulating of mesenchymal markers, e.g., ZEB1, which in turn is dependent on YAP/TAZ activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous study, [ 17 ] we propose that cancer cell clusters with an increasing amount of unjammed cells lead to decreased stiffness and increased fluidity . A recent study [ 97 ] has shown that on the cellular level, the repeated mechanical deformations associated with tissue fluidization by unjamming trigger mechano‐protective mechanisms that lead to the formation of perinuclear actin rings and result in increased nucleus size and stiffness and furthermore, that due to the increased stress and strains unjammed cells are more prone to nuclear envelope rupture and consequential DNA damage, which further increases their malignancy. The unjammed cells showed also an upregulating of mesenchymal markers, e.g., ZEB1, which in turn is dependent on YAP/TAZ activity.…”
Section: Discussionmentioning
confidence: 99%
“…The unjammed cells showed also an upregulating of mesenchymal markers, e.g., ZEB1, which in turn is dependent on YAP/TAZ activity. [97] The activation of YAP, the Yes-associated protein and the highly related transcriptional coactivator with PDZ-binding motif (TAZ) is deemed essential for the initiation or growth of most solid tumors. [98] Since unjamming can occur both within [21] and on the interface of clusters with the ECM, [99,100] these interactions between clusters and ECM may complicate the relationship between fluidity and stiffness further and lead to emergent effects that are discussed in more detail below.…”
Section: Cellular Unjammingmentioning
confidence: 99%
“…The persistence of NE rupture, which is frequently associated with pathological conditions compromising either the functionality or the protein abundance of Lamin A/C 17,[22][23][24][25][26] , triggers DNA damage and the cGAS-STING pathway, an innate immune signaling activated by cytosolic dsDNA 16,17,27,28 . Indeed, it has been reported that in many physiological and pathological conditions, the recurrent loss of NE integrity initiates the cGAS-STING cascade, which leads to a diversity of cellular functions, including type I interferon response, inflammasome activation, and cell death pathways [29][30][31] . The contribution of the nuclear fragility in determining which kind of cellular response will be activated downstream to cGAS-STING pathway has yet to be determined.…”
Section: Mainmentioning
confidence: 99%
“…The understanding of the crucial role played by the mechanical properties in cells and tissues during their physiological and pathological development 7 , pushed Brillouin spectroscopy towards the transition from materials science [8][9][10][11] to life science. In this context, Brillouin spectroscopy demonstrated its ability in a large variety of biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Brillouin spectroscopy demonstrated its ability in a large variety of biological samples. Just to name a few, it has been successfully applied in the investigation of living cells 7,[12][13][14] , in cellular aggregates 15 , in the analysis of complex biological tissues [16][17][18][19][20] , as well as in the characterization of biomimetic materials 21 with innovative properties 22 . The awareness of the great potentiality of the Brillouin characterization in biomedical science is growing more and more, till to deserve its mention among the 10 most important science stories of 2022 reported by "The Guardian" 23 .…”
Section: Introductionmentioning
confidence: 99%